The cost of caring for young children - Dan T. Rosenbaum; Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2005)
This study examines the cost burden of child care, defined as day care expenses divided by after-tax income. Data are from the wave 10 core and child care topical modules to the 1996 Survey of Income and Program Participation. We estimate that the average child under six years of age lives in a family that spends 4.9 percent of after-tax income on day care. However, this conceals wide variation: 63 percent of such children reside in families with no child care expenses and 10 percent are in families where the cost burden exceeds 16 percent. The burden is typically greater in single-parent than married-couple families but is not systematically related to a measure of socioeconomic status that we construct. One reason for this is that disadvantaged families use lower cost modes and pay less per hour for given types of care. The cost burden would be much less equal without low cost (presumably subsidized) formal care focused on needy families, as well as government tax and transfer policies that redistribute income towards them.
Keywords: J13; J18; J22; 330; child care; cost burden; socioeconomic status; Haushaltseinkommen; Kinderbetreuung; Kosten; Soziale Lage; USA